Perceptions and experiences of care providers as clients of NaviCare/SoinsNavi: a patient navigation centre for children and youth with complex care needs. Issue 1 (22nd June 2022) - Thevathasan, Naythrah; Luck, Kerrie E; Luke, Alison; Doucet, Shelley
Abstract : Objective: NaviCare/SoinsNavi is a bilingual patient navigation centre for children and youth 25 years of age or younger with complex care needs in New Brunswick. This research-based centre employs two bilingual patient navigators, one a registered nurse and the other a lay navigator, who assist children/youth, family members and the care team by facilitating more convenient and integrated care using a personalised family-centred approach. The purpose of this study was to explore the perceptions and experiences of care providers who use NaviCare/SoinsNavi. This study builds on ongoing research exploring the experiences of children/youth and their families who are clients of NaviCare/SoinsNavi. Methods: Interviews were conducted with 10 care providers (n=10) from various sectors including social support services (n=6), primary care (n=2), mental health services (n=1) and acute care (n=1). Results: Qualitative interviews were conducted and five themes related to the participants' perceptions and experiences with NaviCare/SoinsNavi emerged, including : (1) trusted source, (2) connector, (3) capacity builder, (4) partner and (5) time saver. The overall impression of NaviCare/SoinsNavi was positive in the service's ability to help support care providers and streamline the care they provide to their clients. Conclusions: It is within every healthcare provider's scope of practice to provide navigational support to essential programmes and services; however, due to limitations in time, resources and capacity, services such as NaviCare/SoinsNavi can be used to help close gaps in care that exists for children/youth with complex care needs and their families.